Sekolah Adat sebagai Basis Politik Identitas : Refleksi Identitas Sosial Pemuda Osing di Banyuwangi - Anisa Andiana W.S; Lisa Roselawati; Dinda Putri Maharani; Ajeng Cahya Safitri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The social identity of the Osing indigenous youth in Banyuwangi faces major challenges due to the influence of globalization that often affects local culture. This study aims to explore the role of traditional schools as a political identity space in shaping and reflecting the social identity of Osing youth. Using a qualitative approach and ethnographic methods, this study explores the experiences of youth in their involvement in the Pesinau traditional school. The findings show that traditional schools function not only as a place to preserve local cultural values, but also as a forum for building collective awareness, strengthening identity, and becoming a cultural protection from global domination. Identity as Osing youth is not obtained automatically, but is formed through a process of reflection, active participation, and negotiation of meaning in daily cultural activities. Traditional schools support the transformation of local values into adaptive contemporary expressions through the use of digital media, art, and education that are appropriate to the context. In this way, traditional schools play an important role as institutions in maintaining the continuity of cultural identity while creating innovative spaces for indigenous youth to face the challenges of the modern era.